2021
DOI: 10.34084/bshr.1007747
|View full text |Cite
|
Sign up to set email alerts
|

Bruselloz Konulu Yayınların Global Analizi ve Türkiye’den Yapılan Yayınlarla Karşılaştırılması

Abstract: ÖzAmaç Bruselloz dünya genelinde en yaygın zoonotik hastalıklardan olup, birçok organ tutulumu yapıp önemli düzeyde morbiditeye neden olmaktadır. Bu çalışmada, bruselloz konulu bilimsel literatürün gözden geçirilmesini ve Türkiye' den yapılan yayınların kıyaslamalarını yapmayı amaçladık. Materyal ve MethodYayınların analizi için Scopus bibliyometrik veri tabanında tarama yapıldı. Başlık, özet ve anahtar kelimelerinde "brucellosis" veya ''Brucella spp. '' "Article" anahtar kelimeleri içeren, 1930-2021 yılları a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It can also provide details on research clusters, current topics of interest, and emerging topic trends. Visualization techniques can be used to analyse and map a variety of databases (Dindar Gürler et al, 2021;Köylüoğlu et al, 2021;Küçük et al, 2021;Mızrakçı et al, 2021;Özlü, 2021;Akyüz et al, 2022;Durgun et al, 2022). In this study both visualization techniques and data analyses were done.…”
Section: Discussionmentioning
confidence: 99%
“…It can also provide details on research clusters, current topics of interest, and emerging topic trends. Visualization techniques can be used to analyse and map a variety of databases (Dindar Gürler et al, 2021;Köylüoğlu et al, 2021;Küçük et al, 2021;Mızrakçı et al, 2021;Özlü, 2021;Akyüz et al, 2022;Durgun et al, 2022). In this study both visualization techniques and data analyses were done.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing extremely early information with the public, researchers, government organizations, institutes, and at national and international levels is of considerable interest. Safety measures and guidelines are implemented based on this type of information [11][12][13][14][15][16][17][18][19][20] . A few bibliometric studies have been performed on research relating to rotavirus 19,20 , but no similar studies on rotavirus vaccine have been published yet.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analyses aid in revealing the state of a certain eld of science as well as in uencing next studies [11][12][13][14][15][16][17][18][19][20] . e rotavirus vaccine has been the subject of several excellent scienti c investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the highest number of papers was in 2002.Focusing specifically on canine brucellosis, our study reveals a rising trend in the number of publications since 2011, with the highest number of articles (n=17) published in 2012 and 2014. This indicates a growing interest and recognition of the importance of studying this zoonotic infection Mizrakci et al (2021). identified a total of 8,903 articles on brucellosis spanning the years 1930 to 2021, while Destani et al (2022) extracted 816 scientific publications on brucellosis conducted by Iranian researchers until 2020.…”
mentioning
confidence: 99%